Artificial Intelligence with Python Cookbook : Proven recipes for applying AI algorithms and deep learning techniques using TensorFlow 2.x and PyTorch 1.6 /: Proven recipes for applying AI algorithms and deep learning techniques using TensorFlow 2.x and PyTorch 1.6. (2020) - Auffarth, Ben
No abstract available